Repository Management Strategy In High School Of Agricultural And Agrobusiness Library (STIP-AP) - Iqlima; Laila Rohani; Khoirul Jamil (International Journal of Cultural and Social Science, 2022)
This research is about the repository management strategy in the Library of the College of Agricultural and Plantation Sciences (STIPAP). The purpose of this research is to find out how the strategy of managing the repository in the STIPAP library. This study uses a qualitative descriptive approach with data collection techniques interview, observation and documentation. The research informants were the head of the STIPAP library and staff librarians. The results of the study show that in managing the repository in the Stipap library, the electronic collection is in the form of CD (softcopy) and hardcopy which is stored in the archive cabinet. The content contained in the STIPAP repository is 2837 Final Project titles, 57 Journal Titles, and 53 Final Project Titles. The STIPAP library does not digitize it, because it accepts soft copies from students. The strategy for managing the Stipap repository is with the role of HR (librarian) in managing the repository, information technology assistance to build the repository, and preservation of digital collections so that the collection can continue to be utilized.